Titanium dioxide (TiO2) nanoparticles improved morpho-physiological characters and DNA content in Swietenia macrophylla an IUCN red listed endangered plant species - Verma, Deepak Kumar; Thakor, Alpesh B.; Patel, Sapan (Current Botany, 2024)
There is a great need to improve plant resilience to unpredictable environmental stresses; therefore, understanding the leading role of Titanium dioxide (TiO2) nanoparticles in alleviating plant stress is crucial for the development of abiotic stress-tolerant endangered plant species. Recently, many new methods have emerged to synthesize nanoparticles, among which the biosynthesis method deserves more attention due to its features such as being eco-friendly, and cost-efficient. The aim of the present study is to perform green synthesis of nanoparticles from extracts and investigate the effect of these nanoparticles on plants. The complete shape and size of the synthesized nanoparticles were analyzed by UV-visible spectroscopy (UV-Vis), Particle Size Analysis (PSA), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) modern instruments. The absorption peak at 310 nm wavelength obtained from UV–Visible spectroscopy analysis confirmed the synthesis of TiO2 nanoparticles (NPs). The presence of strong and broad peaks in FTIR indicated the presence of phytochemicals functional groups and the presence of NPs. SEM result showed that most of the synthesized nanoparticles had spherical angular structure and their size was 75 nm. The effects of TiO2 NPs on Swietenia macrophylla L. an endangered plant species listed in IUCN (International Union for Conservation of Nature) showed that seed germination and plant survival rates were higher than control plants and there was also significant variation in root and shoot development and growth of leaves. The growth rate of the plants was significant compared to control and the chlorophyll pigments content was also recorded significant in the treated plants. The 21 phytochemicals were identified in the plant leaves analyzed with GC-MS. The ISSR analysis result showed polymorphic DNA a band which was as mutants in phenotypic characters of plants. Flow cytometric results had shown that DNA replicate content was increased due to TiO2 NPs effect in plants treated with 200 mgL-1 showed the higher plant growth efficiency.